Hubungan Antara Aktivitas Fisik Dengan Risiko Jatuh Pada Lanjut Usia Di Desa Pucangan Kecamatan Kartasura - Gunawan, Juhendri Dwi Adi, Agus Sudaryanto, S.Kep., Ns., M.Kes (2016)
Elderly is the final stage which will be passed by each individual for their body's aging process. A people get older, their physical, psikologic, social function can decrease. One of the several health promblem in elderly is a fall risk. Poor of physical activity and impired balance can improve fall risk in elderly. The purpose of the study was to indentify the relationship between physical activity and fall risk in elderly at Pucangan Village Kartasura Sub-distric. Classified as a quantitative research with cross sectional approach. The subjects were 82 between age 65 to 75 years (71 female, 11 male) proposional random sampling were selected. Physical activity and fall risk was evaluated using self questioner. The score relationship between physical activity and fall risk were examined by chi square. A result was found have a relatiionship between physical activiy and fall risk in elderly (p-value = 0,010), that mean Ho Rejected. This study showed have relationship between physical activity and fall risk in elderly at Pucangan village Kartasura Sub-distric. Key words : physical activity, risk, fall, elderly